2018
DOI: 10.3389/fphar.2018.01085
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics-Driven Elucidation of Cellular Nitrate Tolerance Reveals Ascorbic Acid Prevents Nitroglycerin-Induced Inactivation of Xanthine Oxidase

Abstract: Glyceryl trinitrate (GTN) has found widespread use for the treatment of angina pectoris, a pathological condition manifested by chest pain resulting from insufficient blood supply to the heart. Metabolic conversion of GTN, a nitric oxide (NO) pro-drug, into NO induces vasodilation and improves blood flow. Patients develop tolerance to GTN after several weeks of continuous use, limiting the potential for long-term therapy. The mechanistic cause of nitrate tolerance is relatively unknown. We developed a cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Topical NTG can induce venous and arterial vessel dilation by smooth muscle relaxation of their walls 14 . Although NTG is bioactivated into NO, there are some suggestions that its vasodilator effect is due to a NO-independent mechanism, which is evidenced in recent experimental and clinical studies showing that NO alone cannot exert all of the vasodilatory effects, in turn suggesting that additional vasoactive mechanisms are involved 48,49 . NTG also can exert its vasodilatory action through the activation of endothelial cells to synthesize prostacyclin.…”
Section: Discussionmentioning
confidence: 99%
“…Topical NTG can induce venous and arterial vessel dilation by smooth muscle relaxation of their walls 14 . Although NTG is bioactivated into NO, there are some suggestions that its vasodilator effect is due to a NO-independent mechanism, which is evidenced in recent experimental and clinical studies showing that NO alone cannot exert all of the vasodilatory effects, in turn suggesting that additional vasoactive mechanisms are involved 48,49 . NTG also can exert its vasodilatory action through the activation of endothelial cells to synthesize prostacyclin.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were spun for 10 min at 14,000× g at 4 • C and the supernatant was transferred to mass spectrometry vials (Microsolv, Leland, NC, USA). LC-MS/MS was carried out with a method previously described [6,7,15] with some differences. Briefly, data-dependent acquisition (DDA) in both the positive and the negative ion mode was conducted using a Shimadzu Nexera UPLC system connected to an AB SCIEX TripleTOF ® 5600 mass spectrometer (AB SCIEX, Concord, Canada).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…From metabolomics analyses of zebrafish fed a diet lacking sufficient AA, we established that AA deficiency, which causes oxidative stress, activates the purine nucleotide cycle to regenerate ATP [6]. Recently, we reported that AA prevents cellular 2 of 13 nitrate tolerance in glyceryl trinitate-treated porcine renal epithelial cells, which is relevant to angina [7]. Using a mass spectrometry-based metabolomics approach, we found that AA protects xanthine oxidase from glyceryl trinitrate-induced inactivation, which is relevant because this enzyme plays a role in the conversion of glyceryl trinitrate into the vasoactive metabolite, nitric oxide [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALDH1, was also capable of reducing GTN to biologically active NO (Tsou et al, 2011). Axton and others (Axton et al, 2018) indicated that xanthine oxidase (XO; EC 1.17.3.2) was a critical enzyme for metabolic bio-activation of GTN to NO.…”
Section: Introductionmentioning
confidence: 99%